Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model PBL di Kelas IV SD Negeri 04 Garegeh Kota Bukittiggi - Veni Yeldihati; Zainal Abidin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research is a classroom action research, using qualitative and quantitative approaches. The flow of research includes planning, action, observation and reflection. The subjects of this study were teachers and students of Class IV of SD 04 Garegeh Elementary School, Bukittinggi City. The research instrument was the observation sheet in the form of RPP observation sheet, observation sheet, teacher aspect and observation sheet on student aspects. This study was conducted in two cycles with three meetings.The results of the study showed an increase in the integrated thematic learning process cycle I and cycle II. (a) Cycle I of the first meeting, RPP got a score of 72.22% qualification (C), Implementation on the aspect of the teacher got a score of 78.6% qualification (B), and the implementation of aspects of the student got a score of 78.6% qualification (B) . (b) Cycle I meeting II, RPP got a score of 76.31% qualification (B), Implementation on the aspect of the teacher got a score of 86.2% qualification (B), and the implementation of aspects of the student got a score of 85.71% qualification (B) . (c) Cycle II, RPP gets a score of 91.67% qualification (SB), Implementation on the aspect of the teacher gets a score of 91.42% qualification (SB), and the implementation of aspects of the student gets a score of 92.85% qualification (SB). Thus the problem based learning model can improve the learning process at 04 Garegeh Public Elementary School, Bukittinggi City.